Glacier surges and landforms in a permafrost environment at the tidewater glacier Paulabreen, inner Van Mijenfjorden, Svalbard - Kristensen, Lene (Annals of Glaciology, 2009)
This thesis presents a study of the landsystem of the Svalbard tidewater glacier Paulabreen and its late Holocene surge moraines, focusing on the glaciology and the glacial geology. An active surge of Skobreen/Paulabreen was observed and the glacier dynamics and stress regime was studied using satellite images, a time-lapse movie and photographs. A persistent subglacial conduit was found beneath the medial moraine between Paulabreen and Bakaninbreen, and we postulate that this constrained surge propagation by preventing the spread of pressurized water beyond the channel. Fresh glacial submarine landforms in front of the glacier were studied and related to known glacier front positions since 1898. An older moraine system deposited around 600 yrs BP was studied, and we found that the terrestrial and submarine landforms were very similar. A mud apron found in both environments was interpreted as pushed marine sediments deposited in a slurry in front of the surging glacier. Hummocky moraine was formed mainly by squeezing of sediments into basal crevasses. While de-icing is almost complete in some parts of the 600 yrs BP moraine, more than 30 m of buried glacier ice is found in a lateral part of the moraine, Crednermorenen. This great variance in the ice-core preservation we attribute to a higher supraglacial sediment content at the glacier margins. Water temperature measurements and modelling work suggest that permafrost, defined solely by temperature, probably exist in Van Mijenfjorden, but we have no evidence that the seabed is frozen.